2015
DOI: 10.2174/1871520615666150716105255
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Early Cancer: Genetics or Immunology? Serum Autoantibody Profiles as Markers of Malignancy

Abstract: The search for effective methods for detecting cancers at very early stages is currently a top priority of cancer research. While numerous oncogenes have been identified in and associated with human cancers, the last 50 years of molecular and genetic studies have not led to a breakthrough in either the diagnosis or the treatment of cancers. Therefore, the role of oncogenes in carcinogenesis is still unclear, as is their usefulness in the diagnosis of human cancers. In the present review, we discuss the concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
(27 reference statements)
1
15
0
Order By: Relevance
“…In recent years, many discoveries of serum tumor biomarkers identified by genomic and proteomic techniques have been documented, such as miRNAs [ 22 ], Long noncoding RNAs [ 23 ], Circulating tumor DNAs [ 24 ], circulating tumor cells [ 25 ], and metabolites [ 26 ]. However, few of these biomarkers for early cancer detection have surpassed blinded Phase III validation studies and have been applied to the clinic over the past two decades [ 11 , 27 , 28 ]. Accumulating evidence of circulating serum autoantibodies in cancer patients highlighted the potential use of autoantibody in early detection [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many discoveries of serum tumor biomarkers identified by genomic and proteomic techniques have been documented, such as miRNAs [ 22 ], Long noncoding RNAs [ 23 ], Circulating tumor DNAs [ 24 ], circulating tumor cells [ 25 ], and metabolites [ 26 ]. However, few of these biomarkers for early cancer detection have surpassed blinded Phase III validation studies and have been applied to the clinic over the past two decades [ 11 , 27 , 28 ]. Accumulating evidence of circulating serum autoantibodies in cancer patients highlighted the potential use of autoantibody in early detection [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autoantibodies against tumor-associated antigens (TAAs) were initially identified in the sera of melanoma patients in 1977 [ 8 ], and have drawn significant attention as they have created chances to develop a source of biomarkers based on the immune system and could be detected at early onset of the cancer disease. Over the past two decades, many studies have demonstrated the potential utility of autoantibodies for cancer lies in the role of early detection, which might supplement current screening strategies to aid early cancer diagnosis [ 9 11 ]. However, the relationship between sera autoantibodies and EJA has not been well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…These antigens may trigger the immune system to produce high titers of autoantibodies or tumor-associated autoantibodies (TAABs). These TAABs can be promising biomarkers for early diagnosis of breast cancer based on concentration, which may precede clinical confirmation of cancer by months to years, as the detection of autoantibodies can be performed earlier than the originating tumor-associated antigens (TAAs) assays [ 2 , 32 , 33 ]. Moreover, there are a plethora of TAABs, which are highly stable in serum and whole-blood compared to other polypeptides [ 34 ].…”
Section: Autoantibodies In Breast Cancermentioning
confidence: 99%
“…The quote and metaphor "an apple found in a car is not synonymous of proof that apples grow in cars" [18] by using an image ( Fig. 1) [18,19] illustrates why "genetic studies have not led to a breakthrough in either the diagnosis or the treatment of cancers" [20].…”
Section: Introductionmentioning
confidence: 99%